Hubungan Motivasi Kerja dan Kecerdasan Emosional dengan Kinerja Pegawai Unit Pelatihan Kesehatan Provinsi Sumatera Utara - Novita Rizky Dalimunthe; Syaiful Akhyar Lubis; Azhar Aziz (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
This study aims to determine the relationship of work motivation and emotional intelligence with the performance of Health Officers UPT Province of North Sumatra. The type of this research is quantitative research with research population of UPT Health officer of North Sumatera Province as many as 66 people and all of them used as sample (total sampling). The result of analysis shows that the average of work motivation, emotional intelligence and performance of UPT Health officer of North Sumatera Province is high. The results of multiple regression analysis based on the first hypothesis shows that there is a significant relationship between work motivation and employee performance of 0,578 and p 0.000. The second hypothesis shows that there is a significant relationship between emotional intelligence and employee performance of 0.644 and p 0.000. And there is a very significant relationship between work motivation and emotional intelligence with employee performance of 0.726 and p 0.000. The higher the work motivation and emotional intelligence of the UPT Health Officer of the Province of North Sumatra, the higher the performance of the employee. Contribution given work motivation and emotional intelligence to employee performance is equal to 52,7%.